1993
DOI: 10.1007/bf02446883
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance plethysmography: Its use in studying the cerebral circulation of the rabbit

Abstract: Electrical impedance plethysmography (EIP) is a noninvasive method that may be useful for both the continuous and serial measurement of changes in pulsatile cerebral blood volume and perhaps cerebral blood flow (CBF). It has not been well validated by comparison with other methods. To attempt to validate the EIP technique, the relationship between the peak amplitude of the transcranial, cardiac-synchronous impedance waveform (dZp) and cerebral blood flow measured by the radiolabelled microsphere technique (CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Changes in CBF detected by LDF compare well with measurements performed with the hydrogen clearance technique, 9,17,28 microspheres, 5,12,22,29 and the [ 14 C]iodoantipyrine method. 10,14,16 The LDF test does not produce absolute values for blood flow in the microcirculation.…”
Section: Autoregulation Assessment Using Ldf and Cppsupporting
confidence: 64%
“…Changes in CBF detected by LDF compare well with measurements performed with the hydrogen clearance technique, 9,17,28 microspheres, 5,12,22,29 and the [ 14 C]iodoantipyrine method. 10,14,16 The LDF test does not produce absolute values for blood flow in the microcirculation.…”
Section: Autoregulation Assessment Using Ldf and Cppsupporting
confidence: 64%
“…Comparing LDF with the microsphere technique is an appropriate way to validate LDF because microspheres and red cells distribute similarly in the circulation. However, previous studies did not show good absolute agreement of both methods in spite of good correlation (Lindsberg et al 1989; Colditz et al 1993). These systematically differing flow changes detected by LDF seem to occur specifically during lCBF increases while the slope of the regression line between lCBF changes obtained by LDF and 14 C‐iodoantipyrine autoradiography (Dirnagl et al 1989) or hydrogen clearence (Skarphedinsson et al 1988; Haberl et al 1989) is reported as being approximately 0.9 at a reduced lCBF in the adult rat brain.…”
Section: Discussionmentioning
confidence: 71%
“…However, only weak and qualitative-rather than quantitative-correlations were found in all studies in which the Z signal was compared to other robust indicators of cerebral circulation (Jacquy et al 1974, Colditz et al 1988a, 1993.…”
Section: Introductionmentioning
confidence: 90%